IMPLEMENTATION OF MACHINE LEARNING FOR HUMAN ASPECT IN INFORMATION SECURITY AWARENESS - Saridewi, Valentina Siwi; Sari, Riri Fitri (Journal of Applied Engineering Science, 2021)
This research discussed our experienced on building a machine learning model on the human aspect of information security awareness. The model was built through a classification and clustering approach using a broad outline process including importing data, handling incomplete data, compiling datasets, feature scaling, building models, and evaluating models. The dataset was arranged based on the results of a questionnaire referred to as the the Human Aspects of Information Security Questionnaire (HAIS-Q) to Indonesian society. The results of the classification model were evaluated by several methods, including k-fold Cross Validation analysis, Confusion Matrix, Receiver Operating Characteristics, and score calculation for each model. One of the algorithms in the classification used is the Support Vector Machine that has an accuracy performance of 99.7% and an error rate of 0.3%. One of the algorithms in clustering is the DBSCAN which has an adjusted rand index value of always close to 0.
Keywords: classification, clustering, python, information security awareness